Integrity Assessment of Wall Distorted of Buried Gas Pipeline - Wira Herucakra; Luh Putri Adnyani; Lukytoardi Megantoro (Department of Naval Architecture - Diponegoro University, 2023)
In the oil and gas industry, the pipeline is the main mode to transport the product and can be applied for long-distance transportation; hence some pipe segments may be buried underground. Buckling as the main cause of pipeline deformation and failure is often found at the in-service buried pipeline during inspection activity. Changes in laying conditions such as design and operational parameters, human activity and geological movement can affect the redistribution of deformation that may lead to pipe buckling. This paper presents a methodology that integrates inspection results and finite element analysis for the distorted wall of the pipeline. Inspection reported anomaly cases of wall distorted at buried gas pipeline, and the result will be used to do stress analysis using finite element analysis. Three different conditions within the different treatment of bedding conditions were assessed: pipe buried on uncompacted soil, pipe buried with rock bedding, and pipe buried in compacted soil. The result shows that the deteriorated pipe can be considered acceptable when buried in compacted soil. This condition may be used for further action and consideration, such as a mitigation strategy to maintain the safety and integrity of the deteriorated pipe.